Computer-aided approach for the development and characterization of medicated gel blended with Psidium Guajava leaves - Amirah Afifah Kamaruddin (2022)
A phytochemical compound in Psidium Guajava are responsible for treating various health problems and are useful as an antibacterial agent. This study focuses on the extraction method of phytochemical compounds from guava leaves, the analysis of phytochemical compounds in the extraction solvent, and the development of an efficient technique for formulating guava leaves gel for medication purposes by optimizing the operating factors that affect formulation using response surface methodology (RSM) by Design-Expert® Software version 13. The response surfaces approach was utilized to aid in the formulation of the recommendation formula, which included the construction of two elements (independent variables). The ratio of hydroxypropyl methylcellulose (HPMC) (XI) was selected between 0.5 to 3.51777 percent, while the temperature (X2) was set between 48.7868 to 91.2132 degrees Celsius. The pH value (Y1), the viscosity value (Y2), and the droplet size value (Y3) were chosen as factors (dependent variable).